2015
DOI: 10.1016/j.proenv.2015.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Bioactive Substances Extracted from Fresh and Dried Spirulina sp.

Abstract: The increase consumption of natural substances has brought about in increasing demand on biological source, including Spirulina sp. This Spirulina sp. has been recognized to provide some natural substances such as natural colorant, source of vitamins, protein and some minerals. Different material state of Spirulina sp. in the form of fresh and dried form may cause different quantity and quality of natural substances in microalgae which posses a wide range of change including nutritional and natural substances.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 5 publications
5
49
2
9
Order By: Relevance
“…This nutritional composition corresponded to an energetic value of 378 ± 1 kcal/100 g dw. In general, these results corroborate previous reports on the nutritional composition of Spirulina platensis (Agustini, Suzery, Sutrisnanto, Maruf, & Hadiyanto, 2015;Sharoba, 2014), and are in accordance with the ones reported in the commercial label.…”
Section: Nutritional and Chemical Composition Of Spirulina Platensissupporting
confidence: 92%
“…This nutritional composition corresponded to an energetic value of 378 ± 1 kcal/100 g dw. In general, these results corroborate previous reports on the nutritional composition of Spirulina platensis (Agustini, Suzery, Sutrisnanto, Maruf, & Hadiyanto, 2015;Sharoba, 2014), and are in accordance with the ones reported in the commercial label.…”
Section: Nutritional and Chemical Composition Of Spirulina Platensissupporting
confidence: 92%
“…In this study, the EC50 was 23 μg/ml, indicating a very high antioxidant potential [72]. Both the lower EC50 and the higher DPPH activity were related to a high antioxidant activity [73]. e study has been carried out on the DPPH-scavenging activity of the Spirulina extract compared to both vitamins C and E which showed that EC50 was about 40 ppm; i.e., one is better than the other which is comparable, as shown in [71].…”
Section: Antioxidant Bioactivity Analysismentioning
confidence: 48%
“…Spirulina is also rich in non-essential amino acids such as: alanine (5.82%; helps in the strengthening of the cell wall); arginine (5.98%; helps in cleaning the blood); aspartic acid (6.34%; helps to transform carbohydrate into energy); cystine (0.67%; maintains a healthy pancreas and blood glucose level); glutamic acid (8.94%; controls healthy mental function); glycine (3.5%; enhances energy); histidine (1.08%; helps in improving auditory nerves); proline (2.97%; reduces alcohol content in the body); serine (4%; helps to produce improved fatty protection); and tyrosine (4.6%; reduces the process of aging, produces color to the body and protects the body from sun radiation) (Abdel-Tawwab et al, 2008;Agustini et al, 2015;Vo et al, 2015).…”
Section: Ingredients Of Spirulina Ingredientsmentioning
confidence: 99%